Towards free trade in the Western Hemisphere (OAS WashingtonUS, 1994)
Examines alternatives which fall into two broad categories viz. bilateralism and multilateralism. Dicusses the advantages and disadvantages of each alternative. Provides a list of the basic principles that should guide whatever mechanism is choosen to eventually form a hemispheric free trade area.
DC